پرمیشر سنگھ"اورہجرت کی نفسیات (تجزیاتی مطالعہ ) - ڈاکٹر محمد خرم یاسین; ڈاکٹر محمد افضال بٹ (Khayaban - خیابان, 2024)
Abstract Ahmad Nadeem Qasmi, a luminary in Urdu literature, displayed unparalleled versatility as a writer in both prose and poetry. His short stories intricately wove together real-life experiences, blending socio-political, economic, religious, and psychological dimensions. The partition of the Indian subcontinent served as a poignant source for thematic material, with "Parmesher Singh" exemplifying this. In "Parmesher Singh," the narrative revolves around Parmesher Singh and his family, migrants forced by the partition, coping with the profound loss of their son. Amidst the violence against Muslim migrants, Parmesher encounters Akhtar, a boy of his son's age. A poignant bond forms between them, with Parmesher treating Akhtar as a surrogate for his lost child. Attempting to reshape Akhtar's religious identity, Parmesher imparts love and care, but Akhtar remains devoted to his roots. The article explores the psychological intricacies of migrants, parents dealing with the loss of their children, and children navigating the absence of their parents through a detailed analysis of "Parmesher Singh." Embedded in the context of the partition, the article illuminates the psychological complexities, human attitudes, motivations, internal and external conflicts, character duality, chaos, and collective social psychology within Qasmi's evocative storytelling.